IMPLEMENTASI PERDA NOMOR 6 TAHUN 2012 TENTANG PENGELOLAAN SAMPAH DI KOTA SEMARANG - Pamungkas, Dian Ayu; ., Yuwanto; Astrika, Lusia (Journal of Politic and Government Studies, 2014)
AbstractWaste matter in the city of Semarang is an issue that never ends, where is the garbage there will always be for man is still alive. All the activity and human activity never detached and always produces waste. The waste problem in the city of Semarang will be more worried about handling if not be taken seriously. This on land because of carelessness final disposal place at Jatibarang’s landfills more narrow and already full. Even the volume of waste in the flue to this place from year to year experienced significant improvement that is to ride about 10 percent. Semarang City Government has made a policy to resolve the issue that is in the form of Regional Regulations No. 6/2012 about waste management in the city of Semarang.The purpose of this research is to know the implementation of Regional Regulation No. 6/2012 about waste management in the city of Semarang, and supporting factor or factor impediment to the implementation. The methods used in this study is a qualitative approach is descriptive-analytic. There are two indicators in the implementation of waste management, there are management of waste and waste utilization.The implementation of the waste management in Semarang city is still considered less properly, especially the management at Jatibarang’s landfill. Requires support from all parties within petrification deal with waste matter that2has no end. The support of government, privat, and society in encouraging wastemanagement activities are needed in implementing the mandate of regionalregulation No. 6/2012, As well as awareness of the self about the importance ofhealthy environment externalities on the self each.Supporting factors in implementation of waste management in the city ofsemarang are the presence of facilities and infrastructure every year, cooperationbetween state corporations, private and society. While factors impediment toimplementation are communication the lack of space at tpa jatibarang, weatherfactor, and infrastructure of unbalanced production with the rubbish every day.Keywords: Implementation, Regional Regulation, Waste Management.